Effects of succulent poaching on the functional diversity and ecosystem services in the Knersvlakte region, South Africa - Pooe, Otshepeng Lerato Abigail (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScConsEcol)--Stellenbosch University, 2024.